2017
DOI: 10.1038/srep41906
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol-induced changes in PIN2 polarity and auxin transport in the Arabidopsis thaliana rol1-2 mutant require phosphatase activity

Abstract: The phytohormone auxin is a major determinant and regulatory component important for plant development. Auxin transport between cells is mediated by a complex system of transporters such as AUX1/LAX, PIN, and ABCB proteins, and their localization and activity is thought to be influenced by phosphatases and kinases. Flavonols have been shown to alter auxin transport activity and changes in flavonol accumulation in the Arabidopsis thaliana rol1-2 mutant cause defects in auxin transport and seedling development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 61 publications
(120 reference statements)
3
42
0
Order By: Relevance
“…The gene encoding for the second enzyme of the flavonoid biosynthesis pathway, chloroplastic chalcone isomerase, is enriched in L1, while the chalcone synthase gene is enriched in D2. It is known that flavonoids affect the expression, localization and recycling of PINs, as well as the activity of ABCB‐type auxin transporters (Brown et al ; Peer & Murphy ; Bailly et al ; Santelia et al ; Kuhn et al ). The formation of local auxin maxima in SAM depends mainly on the action of PINs at L1, and through this layer, auxin arrives at the organ initiation sites (Vernoux et al ).…”
Section: Stress Adaptation Of Apical Meristemsmentioning
confidence: 99%
“…The gene encoding for the second enzyme of the flavonoid biosynthesis pathway, chloroplastic chalcone isomerase, is enriched in L1, while the chalcone synthase gene is enriched in D2. It is known that flavonoids affect the expression, localization and recycling of PINs, as well as the activity of ABCB‐type auxin transporters (Brown et al ; Peer & Murphy ; Bailly et al ; Santelia et al ; Kuhn et al ). The formation of local auxin maxima in SAM depends mainly on the action of PINs at L1, and through this layer, auxin arrives at the organ initiation sites (Vernoux et al ).…”
Section: Stress Adaptation Of Apical Meristemsmentioning
confidence: 99%
“…It has been found that, in Arabidopsis, mutation of the genes encoding cinnamate 4hydroxylase (C4H) and hydroxycinnamoyl-coenzyme A shikimate:quinate hydroxycinnamoyl-transferase (HCT) involved in this pathway resulted in changes in the structural, developmental, and reproductive phenotypes of Arabidopsis plants [31][32][33]. Interestingly, the flavonols quercetin and kaempferol have been shown to inhibit polar auxin transport and to enhance consequent localized auxin accumulation [34][35][36]. Recently, Kuhn, et al [34] suggested that flavonols could modulate auxin transport by modifying the antagonistic kinase/phosphatase equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the flavonols quercetin and kaempferol have been shown to inhibit polar auxin transport and to enhance consequent localized auxin accumulation [34][35][36]. Recently, Kuhn, et al [34] suggested that flavonols could modulate auxin transport by modifying the antagonistic kinase/phosphatase equilibrium. Therefore, flavonols could affect auxin transport in zigzag-shaped shoots.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that mutation of the genes encoding the cinnamate 4-hydroxylase (C4H) and hydroxycinnamoyl-coenzyme A shikimate:quinate hydroxycinnamoyl-transferase (HCT) involved in this pathway resulted in changes in the structural, developmental, and reproductive phenotypes of plants [39][40][41]. Interestingly, flavonols, quercetin and kaempferol, have been shown to inhibit polar auxin transport and to enhance consequent localized auxin accumulation [42][43][44]. Recently, Kuhn, et al [42] suggested that flavonols could modulate auxin transport by modifying the antagonistic kinase/phosphatase equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, flavonols, quercetin and kaempferol, have been shown to inhibit polar auxin transport and to enhance consequent localized auxin accumulation [42][43][44]. Recently, Kuhn, et al [42] suggested that flavonols could modulate auxin transport by modifying the antagonistic kinase/phosphatase equilibrium. Therefore, flavonols could affect the auxin transport in the zigzag shoot.…”
Section: Discussionmentioning
confidence: 99%